PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PT POS INDONESIA TANGERANG SELATAN - Rayyan Pebriyan Kurbayasi; Ahmad Syukri (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to determine the extent of the influence of motivation and work discipline on employee performance at PT Pos Indonesia Tangerang Selatan. The type of research used is quantitative, with the sampling technique using the saturated sampling method, so the entire population was used as the research sample, totaling 87 respondents. The data collection technique was carried out through the distribution of questionnaires using a Likert scale, then processed using the SPSS version 25 application. Data analysis includes validity and reliability tests, classical assumption tests, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results showed that motivation had a significant effect on employee performance with a simple regression equation of Y = 26.986 + 0.385X₁. The correlation value (R) of 0.352 indicates a low relationship, with a contribution of 12.4%. The hypothesis test proves that tcount > ttable (3.468 > 1.988) and a significance value of 0.001 < 0.05, thus H₁ is accepted. Work discipline also has a significant effect on performance with the equation Y = 26.670 + 0.381X₂. The correlation value (R) of 0.327 indicates a low relationship, with a contribution of 10.7%. The hypothesis test shows that tcount > ttable (3.185 > 1.988) and a significance value of 0.002 < 0.05, thus H₂ is accepted. Simultaneously, motivation and work discipline have a positive and significant effect on employee performance with a multiple regression equation of Y = 13.896 + 0.356X₁ + 0.347X₂. The correlation value (R) of 0.460 indicates a moderate relationship with a contribution of 21.1%, while the remaining 78.9% is influenced by other factors outside the study. The F test results prove that Fcount > Ftable (11.262 > 3.11) with a significance value < 0.05, thus H₃ is accepted.